Pengaruh Promosi dan Harga Terhadap Keputusan Pembelian Rumah Pada Permata Arco Residence - Junita Marcela Putri; Taat Kuspriyono; Lady Diana Warpindyastuti (International Forum of Researchers and Lecturers, 2023)
This research focuses on finding out how much influence promotions and prices have on house purchasing decisions at Permata Arco Residence. In this research, the model used is quantitative with Non Probability techniques using the Purposive Sampling method, namely having a specific research target, and the author conducted research by distributing questionnaires targeting 73 respondents in Likert scale units. Data processing used in this research is using SPSS 26 with multiple linear regression analysis techniques. The results of this research show that promotion (X1) does not have a significant influence on purchasing decisions with a value of 0.239 > 0.05 and a t-count value of 1.187 < t-table 1.993, however price (X2) has a significant influence on purchasing decisions. with sig value. 0.000 < 0.05 and the t-count value is 3.871 > t-table 1.993. Simultaneously promotion and price influence purchasing decisions with a calculated F value of 16.271 > 3.19 F table.